Concrete thermal failure criteria, test method, and mechanism: A review - Zhu, He; Hu, Yu; Ma, Rui; Wang, Juan; Li, Qingbin (Construction & building materials, 2021)
•Failure stress is lower than the tensile strength for concrete thermal cracking.•The unsuitable failure criterion is the main reason for occurrence of concrete thermal cracking.•Stress-Strain combined criterion has demonstrated in evaluating thermal cracking.•Both restrained stress/strain and direct tensile strength/strain are required. The thermal cracking of massive concrete, especially for the dam concrete, due to the complex temperature histories and restraint conditions jeopardizes the structure's safety and durability. Suitable failure criterion is one of the critical factors for preventing thermal cracking. The eligible failure criterion depends on the full understanding of the failure mechanism, which further relies on convincing experimental techniques. Though the mechanisms and experimental techniques of thermal cracking have been extensively studied, their relations to failure criteria are rarely established. Thus this state-of-the-art review focuses on the thermal failure criteria, related to mechanisms and temperature stress test (TST) methods. The TST researches show the restrained concrete exhibits lower failure stress than its direct tensile strength tested by the free specimen, while has a larger failure strain than its tensile strain capacity, leading to disqualification of the conventional tensile strength/strain capacity criterion. The development of a multiple TST machine system enables the establishment and verification of a Stress-Strain combined criterion. Meanwhile, more verifications experiments considering the material compositions, temperature histories, restrained degrees, loading durations should be conducted. Moreover, the three-dimensional failure criteria and TST methods are suggested for future research.